Evaluation of different antimicrobial polymeric coatings for food contact surfaces - Great Iruoghene Edo; Alice Njolke Mafe; Ali B. M. Ali; Patrick Othuke Akpoghelie; Emad Yousif; Endurance Fegor Isoje; Ufuoma Augustina Igbuku; Khalid Zainulabdeen; Joseph Oghenewogaga Owheruo; Arthur Efeoghene Athan Essaghah; Huzaifa Umar; Dina S. Ahmed; et al. (Discover Food)
Abstract With growing concerns over foodborne illnesses and spoilage, ensuring microbial safety in the food industry has become more crucial than ever. This review examines recent developments in antimicrobial polymeric coatings for food contact surfaces, emphasizing their increasing role in minimizing microbial contamination. It aims to classify key coating types which includes natural biopolymers (e.g., chitosan, alginate), synthetic polymers (e.g., polyethylene, polypropylene), and composites and to assess their antimicrobial mechanisms, such as controlled release and contact-killing actions. The review also evaluates various antimicrobial agents, including metal nanoparticles, plant-derived compounds, and synthetic chemicals, for their effectiveness across diverse food systems. Case studies and summarized data demonstrate that natural coatings enhanced with bioactive agents exhibit strong inhibitory effects against pathogens like Escherichia coli, Listeria monocytogenes, and Salmonella sp., particularly under optimized conditions. Environmental factors such as temperature, humidity, and coating thickness are shown to significantly affect antimicrobial performance. Despite notable progress, challenges persist regarding cost, biodegradability, and regulatory approval. The review concludes by underscoring the promise of hybrid biopolymer coatings and green antimicrobial agents in advancing sustainable food packaging, calling for further research into scalable and environmentally friendly solutions.